#MondayNightIBD: Management of Chronic #Pouchitis. Issue 4 (24th August 2020) - Donet, Jean A; Rieder, Florian; Charabaty, Aline
Abstract: We present a #MondayNightIBD case of chronic pouchitis and discuss key diagnostic and therapeutic challenges commonly encountered in clinical practice. We make reference not only to the limited published literature but also to the informed opinions of the #MondayNightIBD discussion participants, identifying gaps where management guidelines and research are needed. A #MondayNightIBD Algorithm for Pouchitis Management is proposed. Lay Summary: Patients with inflammatory bowel disease may develop chronic inflammation of the pouch after intestinal restorative surgery. Our review of the scientific data and the @MondayNightIBD participants' opinions reveals consensus guidelines and research on diagnosis and treatment of this condition are needed.